Critical Current Density in Solid‐State Lithium Metal Batteries: Mechanism, Influences, and Strategies - Lu, Yang; Zhao, Chen‐Zi; Yuan, Hong; Cheng, Xin‐Bing; Huang, Jia‐Qi; Zhang, Qiang (Advanced functional materials, 2021)
Solid‐state lithium (Li) metal batteries (SSLMBs) have become a research hotspot in the energy storage field due to the much‐enhanced safety and high energy density. However, the SSLMBs suffer from failures including dendrite‐induced short circuits and contact‐loss‐induced high impedance, which are highly related to the Li plating/stripping kinetics and hinder the practical application of SSLMBs. The maximum endurable current density of lithium battery cycling without cell failure in SSLMB is generally defined as critical current density (CCD). Therefore, CCD is an important parameter for the application of SSLMBs, which can help to determine the rate‐determining steps of Li kinetics in solid‐state batteries. Herein, the theoretical and practical meanings for CCD from the fundamental thermodynamic and kinetic principles, failure mechanisms, CCD identifications, and influence factors for improving CCD performances are systematically reviewed. Based on these fundamental understandings, a series of strategies and outlooks for future researches on SSLMB are presented, endeavoring on increasing CCD for practical SSLMBs. The critical current density (CCD) is an important standard for future solid‐state Li metal batteries (SSLMBs), which is highly related to power density and fast charge capability. The CCD can help to unravel the rate determining factors of Li kinetics including special mass transport and charge transfer at solid–solid interfaces.